Analysis of bacterial communities in a municipal duck pond during a phytoplankton bloom and isolation of Anatilimnocola aggregata gen. nov., sp. nov., Lacipirellula limnantheis sp. nov. and Urbifossiella limnaea gen. nov., sp. nov. belonging to the phylum Planctomycetes. (12th January 2021) - Kallscheuer, Nicolai; Rast, Patrick; Jogler, Mareike; Wiegand, Sandra; Kohn, Timo; Boedeker, Christian; Jeske, Olga; Heuer, Anja; Quast, Christian; Glöckner, Frank Oliver; Rohde, Manfred; Jogler, Christian
Summary: Waterbodies such as lakes and ponds are fragile environments affected by human influences. Suitable conditions can result in massive growth of phototrophs, commonly referred to as phytoplankton blooms. Such events benefit heterotrophic bacteria able to use compounds secreted by phototrophs or their biomass as major nutrient source. One example of such bacteria are Planctomycetes, which are abundant on the surfaces of marine macroscopic phototrophs; however, less data are available on their ecological roles in limnic environments. In this study, we followed a cultivation‐independent deep sequencing approach to study the bacterial community composition during a cyanobacterial bloom event in a municipal duck pond. In addition to cyanobacteria, which caused the bloom event, members of the phylum Planctomycetes were significantly enriched in the cyanobacteria‐attached fraction compared to the free‐living fraction. Separate datasets based on isolated DNA and RNA point towards considerable differences in the abundance and activity of planctomycetal families, indicating different activity peaks of these families during the cyanobacterial bloom. Motivated by the finding that the sampling location harbours untapped bacterial diversity, we included a complementary cultivation‐dependent approach and isolated and characterized three novel limnic strains belonging to the phylum Planctomycetes .